So Why Do You Think That Way?: Examining the Role Implicit Attitudes and Motivation Play in Audience's Perception of a Racially Charged Issue. Issue 4 (2nd October 2017) - Holt, Lanier F.; Ellithorpe, Morgan E.; Ralston, Rachel
Abstract : Events in Ferguson (MO), the Eric Garner incident, and most recently Chicago (IL), have again brought perceptions of race to the forefront of the public's conscience. Often perceptions of racially charged events are split along racial lines with Whites often siding with law enforcement and Blacks seeing a miscarriage of justice. Bifurcated perceptions along racial lines are nothing new, dating back to the early 1900s. Despite this schism, few analyses have examined the genesis of this difference in perceptions on racial issues. This analysis looks to fill that gap. Specifically, we examine the role media frames and people's preexisting attitudes and motivations play in determining what they think of contentious race issues and the people involved in them. Using the Jena Six incident as a case study, we find that people with less egalitarian racial attitudes—and low motivation to hide those attitudes—are less likely to blame race-related problems on mitigating cultural factors. They are also more likely judge news stories about a racial issue as being low quality. However, thematically framed stories that include discussion of the cultural aspects of the event may help to reduce this process.